Enhancing Junior High School Literacy: Incorporating Luwu Cultural Heritage into Reading Materials - Tompo, Dewi Sri; Sahraini, Sahraini; Thayyib, Magfirah (Universitas Hamzanwadi, 2023)
Integrating local culture into language material leads to improving the students’ reading skills. Conducted in South Sulawesi's Luwu Regency, the research employs the ADDIE model for development and assessment. Participants included five English teachers and 25 eighth-grade students from (Junior High School) SMP Negeri 4 Belopa. During the analysis phase, teacher interviews and student questionnaires revealed a strong demand for culturally relevant materials, with 92% of students and 100% of teachers expressing a need for Luwu-based content. Subsequently, the design phase involved selecting texts reflective of local culture, guided by the needs analysis. The development phase produced an initial draft of a reading book comprising four chapters: